Experimental research of radiative heat transfer in a water film. (February 2018) - Kuznetsov, G.V.; Osipov, K.Yu.; Piskunov, M.V.; Volkov, R.S.
Graphical abstract: Highlights: Water with impurities becomes partially transparent for IR when heated. Liquid and solid impurities enhance IR absorption by water. The effect is the strongest for carbonated water versus tap and distilled waters. Optical water properties depend on hydrophobic interaction of amphiphilic molecules. Decreasing of water purification duration and total energy consumption is discussed. Abstract: The paper presents results of experimental research into the transmission of infrared radiation through water film. Experiments substantiate a hypothesis about the considerable role of radiative heat transfer when heating heterogeneous water drops containing opaque solid particles in high-temperature gases. We measure the temperatures of water film surface, the bottom of a cylindrical plastic cuvette and a graphite substrate. During the experiments, the typical thickness of the water film, the bottom of the plastic cuvette and the graphite substrate is 1 mm. The temperature measurements are implemented for carbonated, distilled and tap water. Results of a comparative analysis of these measurements are presented as well. The hypothesis is formulated about a significant variation in the optical properties of water under temperature fluctuations. This assumption is based on the hydrophobic properties of amphiphilic molecules. Importantly, the experimental data enable the study of rapid evaporation of a liquid at internal and external interfaces of water drops containing solid opaque particles with a further explosive fragmentation of water film. This mechanism relies on heating of the particle surface above the boiling point of water.